Regeneration of chronic myocardial infarction by injectable hydrogels containing stem cell homing factor SDF-1 and angiogenic peptide Ac-SDKP - Song, Myeongjin; Jang, Hwanseok; Lee, Jaeyeon; Kim, Ji Hyun; Kim, Soo Hyun; Sun, Kyung; Park, Yongdoo (ELSEVIER SCI LTD, 2014)
Regeneration of chronic myocardial infarction (CMI) is one of the challenging issues due to its limited regeneration activity compared to acute or sub-acute stage. In this study, we examined whether combination of stem cell homing factor (SDF-1) and angiogenic peptides (Ac-SDKP) injected with biomimetic hydrogels promote regeneration of cardiac function in a CMI model. We evaluated the regeneration of chronically infarcted myocardium using injectable biomimetic hydrogels containing two therapeutic factors; stromal-derived factor-1 (SDF-1) and Ac-SDKP for stem cell homing and angiogenesis, respectively. Injection of the two therapeutic factors into the infarct region of the left ventricle showed that the biomimetic hydrogels containing two therapeutic factor exhibited significantly improved left ventricle function, increased angiogenesis, decreased infarct size and greatest wall thickness within the infarct region at 4 weeks post-treatment. From these results, it is clear that hydrogels containing two therapeutic factors showed synergistic effects on regeneration in the chronic heart failure model. In conclusion, these results suggest that combination of stem cell homing factor with angiogenic peptides recruit stem cells to the microenvironments, increase the expression of angiogenic genes, enhance the matured vessel formation and improve the cardiac function in chronic MI. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: CHRONIC HEART-FAILURE; CORONARY-ARTERY-DISEASE; ISCHEMIA/REPERFUSION INJURY; SDF-1/CXCR4 AXIS; PROGENITOR CELLS; CARDIAC-FUNCTION; THERAPY; REPAIR; MODEL; EXPRESSION